The Comparison of Effects between Tai Chi Exercise and Glucosamine Supplementation on Balance in Older Woman with Knee Osteoarthritis - Elham Attari; Elaheh Arab-Ameri; Shahzad Tahmasebi-Brojeni (Vesnu Publications, 2018)
Introduction: Knee osteoarthritis is one of the most common musculoskeletal problems in older women which affects their daily life. It causes balance impairment, and increases the rate of falling in these patients. Therefore, the aim of this study was to compare the effects between tai chi exercise and glucosamine supplementation on the balance of older women with knee osteoarthritis. Materials and Methods: This was a clinical trial study, in which 75 women with knee osteoarthritis (according to the Kellgren and Lawrence scale) were chosen, and randomly assigned into 3 groups of tai chi exercise (performed 3 times a week for 3 month), glucosamine supplementation (3 times a week), and control (no intervention). Before and after interventions, static balance (measured by stabilometer in both open and closed eye) and dynamic balance [measured by timed up and go (TUG) test] were examined. Paired sample t and ANOVA tests were implemented for data analyzing at a significant level of less than 0.050. Results: Tai chi exercise had a significant effect on static [open (t = 9.57, P = 0.001) and closed (t = 5.30, P = 0.001) eye] and dynamic balance (t = 8.54, P = 0.001); supplementation variable had a significant effect only on dynamic balance (t = 2.21, P = 0.040); in control group, there was not any significant difference between before and after intervention. Comparing three groups, the ANOVA test showed a significant difference between the exercise and control group in static [open (P = 0.001) and closed (P = 0.001) eye] and dynamic balance (P = 0.040). Conclusion: It seems that tai chi exercises enhance the balance in older women with knee osteoarthritis. It also could be concluded from the results that only the exercise variable has the significant effect on subject's balance compared to glucosamine supplementation.